The Bachelor of Library Science graduates of the Institute of Library Science, University of the Philippines, AY 1964-1993 an employment profile - Serrano, Florida V. 1959- (1994)
One significant observation of the study is the favorable marketability of the BLS graduates. To ensure that the high regard and positive demand for the graduates will continue, it is recommended that the ILS's methods of teaching and techniques be enhanced and more modern facilities and equipment be introduced. In line with this, a periodic evaluation of the BLS program should be done by the school officials to make it more attuned to recent trends in information technology and in order to keep pace with the demands of the changing world.
The 107 Bachelor of Library Science (BLS) graduates of the Institute of Library Science (ILS) from 1964-1993 were surveyed to obtain an employment profile of these graduates. It aimed to find out the current employment status of the graduates, whether they have employed in occupations for which they have been academically prepared; their entry level into the profession, taking into consideration the level of position they now occupy; and to identify what other employments they have had between the first job and their present job. The research findings show that majority of the respondents are presently employed in academic and special institutions as librarians; some are actively involved in government agencies doing office work; are engaged in business activities; or are in the library education profession. Almost all of the respondents are academically prepared for their job. Many did not experience working in another job aside from their present position because they worked right after graduation and remained with the same firm up to the present time.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: University of the Philippines Diliman. -- Institute of Library Science -- Alumni; University of the Philippines Diliman. -- Institute of Library Science -- Graduate students